(untitled) (Bangladesh Renal Journal, 2026)
Background: Febrile neutropenia (FN) is a leading cause of morbidity and mortality in children with cancer. Prompt empirical antibiotic therapy is the cornerstone of management of FN and time to antibiotic (TTA) administration has been proposed as a quality of care measure. Objective: To evaluate the association between TTA and hospital outcomes in children with cancer having FN. Methods: This prospective observational study enrolled 40 children with cancer having FN (absolute neutrophil count <500/mm³) admitted in the Department of Pediatric Hematology and Oncology, Bangladesh Medical University (BMU), Dhaka, Bangladesh. TTA was categorized as <60 minutes, 60-120 minutes, 120-180 minutes and >180 minutes (up to 24 hours). The primary outcome was a composite adverse event like- hospital mortality, needed admission in pediatric intensive care unit (PICU) within 24 hours or fluid resuscitation ≥≥≥≥≥40 mL/kg within 24 hours; the alternative was a good outcome (discharge in stable condition). Associations were assessed using the Chi-square test and Student’s t-test; odds ratios (OR) with 95% confidence intervals (CI) were calculated accordingly. Results: Mean age of the study children was 64.2±34.6 months and 62.5% were male. Acute lymphoblastic leukemia (ALL) was the commonest diagnosis (70%). TTA was <60 minutes in 67.5% of children and early TTA (<120 minutes) was achieved in 82.5% cases. The composite adverse outcome occurred in 6 children (15%); hospital mortality was 7.5%. Early TTA was significantly associated with a favorable outcome compared with delayed TTA (ccccc²=11.82, df=1, p<0.001). TTA <60 minutes was strongly associated with a good outcome (OR 16.25, 95% CI 1.42-185.7, p=0.003). Urinary tract infection, bacteremia and respiratory tract infection were each significantly associated with adverse outcome (p<0.001), whereas cancer type and laboratory parameters or antibiotic regimen were not associated with outcomes. Conclusion: Early empirical antibiotic administration particularly within 60 minutes of presentation was associated with improved hospital outcomes in children with cancer having FN. The findings support TTA as an actionable quality of care target in pediatric oncology including in resource limited settings. Bang. Renal J. 2026; 8(2): 79-85